EVALUATION OF BIOSURFACTANT PRODUCING AND ANTIMICROBIAL RESISTANCE PSEUDOMONAS FOR HEAVY METALS TOLERANCE - Al-Sajad M. S.; H. A. A. Alsalim (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study aimed to evaluate biosurfactant production and antibiotic resistance in Pseudomonas bacteria isolated from some agricultural fields to detect the relationship of these isolates traits with some heavy metals resistance. Bacterial isolates were screened for biosurfactant production through blood hemolysis, oil spreading, emulsification activity, and surface tension. The antibiotic sensitivity was determined using disk diffusion method. Then, identification of the selected isolates and subjected to gradient concentrations of heavy metals to determine the minimum inhibitory concentration (MIC). Biosurfactant production was found in 74.29% of these isolates. The isolates resistance to Ticarcillin-clavulanate, Aztreonam, Piperacillin, and Imipenem were 92.86%, 31.43%, 2.86% and 1.43%, respectively. The eight selected isolates were identified by biochemical tests and VITEK 2 system as P. aeruginosa. The resistance of these isolates to heavy metals differed significantly. The isolate B49 recorded the highest resistance to Cu (MIC=3200 µg/ml) and Zn (MIC=2600 µg/ml), while the isolate B66 recorded the highest resistance to Cd (MIC=1000 µg/ml) and isolate B25 had higher resistance to Hg (MIC=80 µg/ml), and Pb (MIC=2800 µg/ml). The correlation coefficient between emulsification (E24%) and CdCl2 (r=0.27) and Pb (r=0.38) was significant positive, while E24% had a significant negative correlation with Zn (r= -0.63) and non-significant correlation to copper (r=0.02) and mercury (r=0.19) resistance.